2022
DOI: 10.1111/aej.12614
|View full text |Cite
|
Sign up to set email alerts
|

Application of computer‐assisted dynamic navigation in complex root canal treatments: Report of two cases of calcified canals

Abstract: Root canal treatment and non-vital bleaching of teeth with pulp canal obliteration may represent a complex challenge to the clinician. This report describes the usefulness of the computer-assisted dynamic navigation system for the root canal treatment of two cases of teeth with a history of traumatic injury, extensively obliterated root canals and crown discoloration. Clinical and cone-beam computed tomographic evaluations were completed prior to procedures and 12 months after treatment. Both cases were treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…From the 37 selected case reports ( Table 2 ), 25 of them had at least one year of follow-up with excellent results in terms of the absence of symptomatology or evidence of bone regeneration [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Eighteen of them were performed with only single-rooted teeth [ 3 , 9 , 38 , 40 , 44 , 46 , 50 , 51 , 52 , 53 , 55 , 58 , 60 , 61 , 62 , 63 , 64 , 65 ]. In twenty-five of them, GE was used for the treatment of pulp obliteration [ 3 , 9 , 35 , 36 , 37 , 38 , 39 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the 37 selected case reports ( Table 2 ), 25 of them had at least one year of follow-up with excellent results in terms of the absence of symptomatology or evidence of bone regeneration [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Eighteen of them were performed with only single-rooted teeth [ 3 , 9 , 38 , 40 , 44 , 46 , 50 , 51 , 52 , 53 , 55 , 58 , 60 , 61 , 62 , 63 , 64 , 65 ]. In twenty-five of them, GE was used for the treatment of pulp obliteration [ 3 , 9 , 35 , 36 , 37 , 38 , 39 ,…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen of them were performed with only single-rooted teeth [ 3 , 9 , 38 , 40 , 44 , 46 , 50 , 51 , 52 , 53 , 55 , 58 , 60 , 61 , 62 , 63 , 64 , 65 ]. In twenty-five of them, GE was used for the treatment of pulp obliteration [ 3 , 9 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 54 , 58 , 60 , 63 , 64 , 65 ], eight for osteotomy and apicoectomy [ 57 , 59 , 61 , 66 , 67 , 68 , 69 , 70 ], two for re-treatment or removal of fiberglass posts [ 43 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst, the financial outlay to the acquisition of expensive equipment may constitute the main limitation, and the time for case preparation and planning is something greater than that of the free‐hand surgery, the use of this technology in the clinical practice has the potential of shortening the actual surgical time. Additional drawbacks related to the dynamic navigation system used in this clinical case include the fact that it is bulky and requires different extra‐oral devices as well as some level of skill, visuomotor coordination, and practice to achieve accurate instrument placement from entry point to target display on the computer screen (Villa‐Machado et al., 2022). Notwithstanding, it is important to point out that Navident® system has the advantage over other systems such as X‐Guide® (X‐Nav® Technologies, Lansdale, Pennsylvania) in that it is handpiece‐independent.…”
Section: Discussionmentioning
confidence: 99%
“…Although it was reported that canal obliteration in pulpotomised teeth without apical periodontitis does not need any further treatment requirement, it is still a matter of concern [46]. Although recent approaches like the application of computer‐assisted dynamic navigation in complex root canal treatments, and guided endodontics may potentially overcome these problems, the expenses of the equipment and the need for a certain level of expertise and experience of the operator should be considered [47]. Developing advanced diagnostic tools for evaluating the pulpal inflammation level, targeted/specialized biomaterials, and robust comparative evidence for evaluating the outcomes of vital pulp therapies were overemphasized in a recent review [48].…”
Section: Conventional and Tissue Engineering‐based Vital Pulp Treatmentmentioning
confidence: 99%